Diverse effects of the cyclin-dependent kinase inhibitor bohemine: Concentration- and time-dependent suppression or stimulation of hybridoma culture - Franek, F; Strnad, M; Havlícek, L; Siglerová, V; Fismolová, I; Eckschlager, T (Cytotechnology, 2001)
An analog of aromatic cytokinins, the 2,6,9-trisubstituted purine derivative bohemine, was applied to cultures of mouse hybridoma cells in order to analyze its capacity of suppressing cell growth and maintaining or enhancing the production of monoclonal antibody. Addition of bohemine at concentrations in the range of1-10 muM resulted in a short-term arrest of growth and of monoclonal antibody production. The short-term suppression of cell functions was followed by a significant temporary increase of specific growth rate and of specific production rate. The steady-state viable cell density values, found in semicontinuous cultures, showed a certain stimulation of cell growth in the range of micromolar concentrations of bohemine, and inhibition of growth at 10 and 30 muM concentrations. The profiles of cell cycle phases indicated that hybridoma cells are retarded both at the G(1)/S boundary and at the G(2)/M boundary, depending on bohemine concentration. The existence of the sequence of events,from suppression to stimulation, suggests that bohemine probably modulates more than one regulatory pathway in the cell.